Ethnobotanical survey and scientific validation of liver-healing plants in northeastern Morocco - Bencheikh, Noureddine; Elbouzidi, Amine; Baraich, Abdellah; Bouhrim, Mohamed; Azeroual, Abdelhamid; Addi, Mohamed; Mothana, Ramzi A.; Al-Yousef, Hanan M.; Eto, Bruno; Elachouri, Mostafa (Frontiers in Pharmacology, 2024)
Introduction Liver diseases represent a significant global health challenge, with primary causes including excessive alcohol consumption, infections, chemotherapy, and autoimmune disorders. Medicinal plants, due to their natural bioactive compounds, hold promise for developing effective treatments and preventive measures against liver ailments. This study aimed to document the use of herbal remedies in northeastern Morocco for liver diseases and correlate these uses with scientific evidence through a bibliometric analysis. Methods An ethnobotanical survey was conducted in remote communities of northeastern Morocco from October 2020 to January 2022. A total of 189 informants were interviewed using semi-structured questionnaires to gather information on local medicinal plants used for liver ailments. The data were analyzed using four ethnobotanical quantitative indices: use value (UV), familial use value (FUV), informant consensus factor (ICF), and fidelity level (FL). Additionally, a bibliometric analysis was performed to evaluate the scientific support for the ethnopharmacological uses documented. Results The survey identified 45 plant species from 26 different families used in the treatment of liver diseases. The most frequently utilized species were Cuminum cyminum L. (UV = 0.1065), Allium sativum L. (UV = 0.1015), Salvia officinalis L. (UV = 0.0761), Asparagus officinalis L. (UV = 0.0558), and Ziziphus lotus (L.) Lam. (UV = 0.0457). The Apiaceae family showed the highest familial use value (FUV = 0.1066), followed by Alliaceae (FUV = 0.1015). Liver congestion had the highest informant consensus factor (ICF = 0.83), followed by hepatic colic (ICF = 0.80). Bibliometric analysis revealed that 61% of the plants identified had documented pharmacological effects related to liver health. Discussion The study demonstrates that traditional knowledge in northeastern Morocco encompasses a rich diversity of medicinal plants used to treat liver diseases. The high ICF values indicate a strong consensus among informants on the efficacy of these remedies. The correlation between ethnopharmacological use and scientific validation for a significant portion of these plants suggests their potential as reliable therapeutic agents for liver conditions. However, further scientific investigations are necessary to confirm their efficacy and safety in clinical settings. This research contributes valuable information for future studies on the therapeutic potential of these plants. Conclusion This ethnobotanical survey provides a comprehensive database of medicinal plants used in northeastern Morocco for liver diseases. The findings highlight the potential of these plants in developing novel treatments for hepatic conditions, although further research is essential to substantiate their therapeutic claims.